Evaluating the growth potential of Vigna radiata (green gram) using Albizia amara (AA) and Leucaena leucocephala (LL) as a phytoremediator for textile dye (Navy blue dye) simulated soil - Sudarmani Gayathri, N.; Jayanthi, V. (Journal of Plant Stress Physiology, 2016)
Â Soil pollution due to textile dye affects the soil fertility, is a cause for demand crop production in agriculture. The present investigation was to evaluate the growth level of Vigna radiata (green gram) before and after simulation of dye in soil. Germination, biometric evaluation (root length, leaf area, shoot length and plant height) and biochemical activity (Total protein, amino acids, DNA, total carbohydrate and amylase activity) were analyzed. All the process carried out with 1% concentration of dye to assess remediating capacity of plant biomass Albizia amara (AA) and Leucaena leucocephala (LL). Use of these adsorbents as phytoremediator could enhance the binding capacity of blue dye to a great extent shows the phytotoxicity of dye upto 1% in soil.